Follow-up outcomes of asymptomatic brucellosis: a systematic review and meta-analysis. Issue 1 (31st December 2023) - Li, Fande; Du, Lanping; Zhen, Hua; Li, Mujinyan; An, Shuqi; Fan, Wenqi; Yan, Yuke; Zhao, Meifang; Han, Xin; Li, Zhuo; Yang, Huixin; Zhang, Cui; et al.
ABSTRACT: Balancing the potentially serious outcomes of asymptomatic brucellosis and "waiting" for treatment in clinical practice is an urgent issue. Therefore, we assessed the follow-up outcomes and epidemiological characteristics of asymptomatic brucellosis in the absence of treatment to provide evidence-based clinical clues. We searched eight databases in which 3610 studies from 1990 to 2021 were related to the follow-up outcomes of asymptomatic brucellosis. Thirteen studies, involving 107 cases, were finally included. Regarding the follow-up outcomes, we examined the presence or absence of symptoms and decreased serum agglutination test (SAT) titre. During the 0.5–18 months follow-up period, the pooled prevalence of appearing symptomatic was 15.4% (95% CI 2.1%–34.3%), cases that remained asymptomatic were 40.3% (95% CI 16.6%–65.8%), and decreased SAT titre was observed in 36.5% (95% CI 11.6%–66.1%). Subgroup analysis indicated that the pooled prevalence of appearing symptomatic with follow-up times of less than 6 months, 6–12 months, and 12–18 months was 11.5%, 26.4%, and 47.6%, respectively. The student subgroup had a higher prevalence of symptoms (46.6%) than the occupational and family populations. In conclusion, asymptomatic brucellosis has a high likelihood of appearing symptomatic and its severity may be underestimated. Active screening of occupational and family populations should be enhanced, and special attention should be paid to high-titre students for early intervention, if necessary. Additionally, future prospective, long-term, and large-sample follow-up studies are essential.